Advances in Cryptology – ASIACRYPT 2007
DOI: 10.1007/978-3-540-76900-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Byzantine Agreement with Faulty Minority

Abstract: Abstract. Byzantine Agreement (BA) among n players allows the players to agree on a value, even when up to t of the players are faulty.In the broadcast variant of BA, one dedicated player holds a message, and all players shall learn this message. In the consensus variant of BA, every player holds (presumably the same) message, and the players shall agree on this message.BA is the probably most important primitive in distributed protocols, hence its efficiency is of particular importance.BA from scratch, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…All known schemes [PW96,BHR07,GGO12] use temporary broadcast in strictly more than one round in the setup phase. We give a broadcast scheme for t < n/2 which requires only 1 round of the temporary broadcast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All known schemes [PW96,BHR07,GGO12] use temporary broadcast in strictly more than one round in the setup phase. We give a broadcast scheme for t < n/2 which requires only 1 round of the temporary broadcast.…”
Section: Discussionmentioning
confidence: 99%
“…The number of bits broadcast by their protocol in the setup phase is Ω(n 6 κ). Another construction by Hirt et al [BHR07] yields a broadcast scheme for t < n/2 which needs Ω(n) rounds of temporary broadcast with Ω(nκ) bits broadcast in the setup phase. 2 This paper gives the first information-theoretically secure broadcast scheme that requires only 1 round of the temporary broadcast in the setup phase for t < n/2, which is trivially optimal.…”
Section: Contributionsmentioning
confidence: 99%
“…In particular, often in our sub-protocols a player p i is instructed to send a message m to some p j along with his signature sig i (m) on it, so that p j has a proof that he indeed got this message from this sender in the corresponding round 6 . However, if p i is passively corrupted, the adversary might introduce into the protocol arbitrary signatures with signer p i .…”
Section: Remark 2 (The Use Of Signatures)mentioning
confidence: 99%
“…This model has been extensively studied [10,29,12,8,9,2,17] and protocols with optimal resiliency and complexity (communication and computation) polynomial in the number of players were suggested. Later solutions [11,4,28,6] considered a setting where a setup allowing digital signatures is available, and showed that Broadcast tolerating an arbitrary number of cheaters (t < n) is possible, whereas Consensus is possible if and only if t < n/2; for both primitives corresponding protocols with optimal resiliency and complexity polynomial in the number of players were suggested 2 . Lamport and Fischer [25] considered an adversary who can fail corrupt up to t players, and showed that any n − 1 players being fail corrupted can be tolerated for Broadcast.…”
Section: Introductionmentioning
confidence: 99%
“…The number of broadcast rounds in the [PW96] setup construction is O(n 2 ), and it works for an arbitrary number of corruptions (t < n). This was later improved to O(n) broadcast rounds by Beerliová-Trubíniová et al in [BTHR07], at the price of tolerating t < n/2 corruptions, and recently by Hirt and Raykov to just 1, as mentioned above. However, the overall round complexity of this construction (as well as that in [BTHR07]…”
Section: Introductionmentioning
confidence: 99%